2020
DOI: 10.1016/j.urology.2019.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Disparities in Academic Urology

Abstract: OBJECTIVE To better understand promotion timelines across gender and race/ethnicity and how academic output impacts promotion in urology. METHODS We examined the 2017 census. An academic subset was asked questions regarding their promotion timeline. We obtained demographic, academic output, and family responsibility data. RESULTS Of 2926 academic urologists who identified a position of Assistant, Associate, or Full professor, 11.2% were women, 75% were White, and 94% were non-Hispanic. Men authored more papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…45 A recent analysis of the 2017 AUA census showed that women took on average 1.2 years longer than men to advance from assistant to associate professor rank, and men were more likely to experience rapid (<4 years) promotion. 45,46 Changes to our academic promotion system are also proposed to facilitate gender equity in leadership position and career advancement for women. Male STEM faculty devote more time to research activities compared to female peers, who commonly spend more time in teaching, mentoring, and service activities.…”
Section: Promotion Criteriamentioning
confidence: 99%
“…45 A recent analysis of the 2017 AUA census showed that women took on average 1.2 years longer than men to advance from assistant to associate professor rank, and men were more likely to experience rapid (<4 years) promotion. 45,46 Changes to our academic promotion system are also proposed to facilitate gender equity in leadership position and career advancement for women. Male STEM faculty devote more time to research activities compared to female peers, who commonly spend more time in teaching, mentoring, and service activities.…”
Section: Promotion Criteriamentioning
confidence: 99%
“…While previous studies have shown a lack of URM urologists in general practice and in academic urology, this study is the first to quantify the shortage of URM urologists in academic leadership positions. 5,7 According to our sample size of 133 urologic leaders, African-Americans represent 9.0%, Hispanics comprise 3.8%, and American Indians/Alaska Natives make up 0.8% of urologists in leadership positions. A deficiency of URM faculty in academic surgery has been demonstrated with 2.9% of academic surgeons and 2% of academic urologists identifying as African American and 3.6% of academic surgeons and 3% of academic urologists identifying as Latino.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, 2.0% of academic urologists are Black and 3.0% are Hispanic, with no current data available on URMs in leadership positions. 5 Studies have shown ethnic and racial diversity in academic medical faculty can foster culturally and structurally competent physicians and lead to an increase in novel ideas. 6 Concordance-defined as a shared identity based on age, sex, or race-between trainees and faculty members may enhance mentorship, which can in turn lead to greater career satisfaction and support.…”
mentioning
confidence: 99%
“…12 Despite continued increase in female urologists, female urologists remain under-represented relative to female patients seeking urologic care, which takes on greater significance given that female general urologists deliver a greater percentage of urogynecologic cases compared to their male counterparts. 13,14 Cross-sectional studies have highlighted lower mortality and readmission rates for Medicare beneficiaries treated by female physicians. 15 Female urologists are also increasingly pursuing academic careers and fellowship training, recruiting and providing mentorship to medical students, which is crucial given that half the graduating medical students are female.…”
Section: Discussionmentioning
confidence: 99%
“…13 While this is likely multifactorial, there should be institutional or national policies to engage in anti-sexism work to ameliorate such promotion disparity and promote faculty retention with instituting ability to stop the promotion clock during maternity leave, or research funding targeted to women, and assigning promotion credit for all contributing roles. 13 Additionally, given that current female and young urologists have significantly different practice pattern than the retiring urologists, there need to be policy changes to draw urologists to fill the gaps of urologic care in non-metropolitan areas. One possible policy change that can draw younger urologists to fill such gap is by providing loan forgiveness options when practicing in rural or non-metropolitan areas.…”
Section: Discussionmentioning
confidence: 99%